2018
DOI: 10.1097/dbp.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Autism Spectrum Disorder: Profiles of Children Who Are Missed

Abstract: Children with ASD missed by screeners had higher scores on developmental testing and lower scores on the ADOS-2; however, children still performed below average on developmental tests. Our findings suggest that a combined screening approach was most effective for identifying children with ASD from a sample group referred for an ASD evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…Hardy et al screened 2,848 toddlers with the ASQ-3 and M-CHAT-R across 20 pediatric sites, used the "monitor and/or fail" cutoff on any domain, the ASQ-3 identified 87% of the children who screened positive on the M-CHAT-R with followup and 95% of those diagnosed with an ASD (27). Beacham et al tested 124 diagnosed with ASD, ASQ-3 identified 82% by the Communication domain and 85% identified by M-CHAT-R, which further confirmed the compatibility of ASQ-3 and M-CHAT-R (28). In this study, the patients who scored "pass" in the Communication domain of ASQ-3 were classified in the low-risk group of ASD, while those who scored "monitor" or "fail" were put in the high-risk group of ASD.…”
Section: Ages and Stages Questionnaires 3rd Edition (Asq-3)mentioning
confidence: 81%
“…Hardy et al screened 2,848 toddlers with the ASQ-3 and M-CHAT-R across 20 pediatric sites, used the "monitor and/or fail" cutoff on any domain, the ASQ-3 identified 87% of the children who screened positive on the M-CHAT-R with followup and 95% of those diagnosed with an ASD (27). Beacham et al tested 124 diagnosed with ASD, ASQ-3 identified 82% by the Communication domain and 85% identified by M-CHAT-R, which further confirmed the compatibility of ASQ-3 and M-CHAT-R (28). In this study, the patients who scored "pass" in the Communication domain of ASQ-3 were classified in the low-risk group of ASD, while those who scored "monitor" or "fail" were put in the high-risk group of ASD.…”
Section: Ages and Stages Questionnaires 3rd Edition (Asq-3)mentioning
confidence: 81%
“…De sus propiedades psicométricas, su confiabilidad de test-retest 0,92, confiabilidad inter-operador 0,93, consistencia interna con alfa de 0,51 a 0,87; aceptable a buena validez de contenido, sensibilidad 0,86, especificidad 0,85, concordancia con otros instrumentos estandarizados 0,86 (11,12) y aceptable a buena validez concurrente con pruebas como el Inventario de desarrollo Battelle y la Escala Bayley de desarrollo infantil; útil además para el seguimiento de prematuros (20)(21)(22)(23)(24). También se ha descrito que podría tener alguna correlación con pruebas desarrolladas para la detección del autismo (25).…”
Section: Materials Y Métodosunclassified
“…Al respecto, la AAP y "Bright futures" recomiendan realizar una vigilancia y evaluación del desarrollo a los 9, 18 y 24 ó 30 meses de edad (8,9); debido a que en estas estas edades transcurren etapas importantes del desarrollo infantil y a la vez se pueden identificar de manera confiable alteraciones de tipo sensorial, motora gruesa y fina, retrasos en las áreas social, lenguaje y cognitivo. Mientras que el tamizaje del trastorno del espectro autista se recomienda realizar a los 18 y 24 meses (9,25).…”
Section: Autor-año/ Tamaño Muestralunclassified
“…A minority of these children meet the threshold to be considered as "at-risk" at 18 months based on screening instruments (Stenberg et al 2014). It is particularly unclear how the phenotypic presentations of these "at-risk" children later diagnosed with ASD differ from those of autistic children who were not identified by gold-standard screening measures and who would hence have been considered as "low-risk" at 18 months (Beacham et al 2018;Øien et al 2018a). Increased knowledge of phenotypic differences associated with screening performance and outcomes is critical for addressing the challenges of identifying a more substantial proportion of children at 18 months that later go on to develop ASD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies, such as studies of infant siblings of children with ASD, have found that early developmental characteristics (fine motor skills at six months) predicted the severity of ASD symptoms both at 18 and 36 months of age (Iverson et al 2019). Other studies have found that combining a screening instrument with a general developmental checklist improved the prediction of a later ASD diagnosis (Beacham et al 2018).…”
Section: Introductionmentioning
confidence: 99%